2020
DOI: 10.1128/aac.02005-19
|View full text |Cite
|
Sign up to set email alerts
|

Equations To Predict Antimicrobial MICs in Neisseria gonorrhoeae Using Molecular Antimicrobial Resistance Determinants

Abstract: The emergence of Neisseria gonorrhoeae strains that are resistant to azithromycin and extended-spectrum cephalosporins represents a public health threat, that of untreatable gonorrhea infections. Multivariate regression modeling was used to determine the contributions of molecular antimicrobial resistance determinants to the overall antimicrobial MICs for ceftriaxone, cefixime, azithromycin, tetracycline, ciprofloxacin, and penicillin. A training data set consisting of 1,280 N. gonorrhoeae strains was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 52 publications
0
53
0
Order By: Relevance
“…1, Supplementary Table 1). We modeled log-transformed MICs using multiple regression on a panel of experimentally characterized resistance markers for the three most clinically relevant antibiotics 5,11,12 (Supplementary Data 1). This enabled us to make quantitative predictions of MIC based on known genotypic markers and to assess how well these markers predicted true MIC values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, Supplementary Table 1). We modeled log-transformed MICs using multiple regression on a panel of experimentally characterized resistance markers for the three most clinically relevant antibiotics 5,11,12 (Supplementary Data 1). This enabled us to make quantitative predictions of MIC based on known genotypic markers and to assess how well these markers predicted true MIC values.…”
Section: Resultsmentioning
confidence: 99%
“…MICs were log 2transformed for use as continuous outcome variables in linear modeling and GWAS. We modeled transformed MICs using a panel of known resistance markers 11,12 and included the recently characterized mosaic mtrCDE alleles 5 and rplD G70D substitution 78 To visualize the continuous MICs using thresholds as on Fig. 1, we binarized MICs using the CLSI resistance breakpoint for ciprofloxacin, the CLSI nonsusceptibility breakpoint for azithromycin, and the CDC GISP surveillance breakpoint for ceftriaxone.…”
Section: Methodsmentioning
confidence: 99%
“…Penicillin and extended-spectrum cephalosporin resistance has been associated with mutations and recombination within the penA, porinB, and ponA genes and the presence of bla and involves a complex interaction [12].…”
Section: Resultsmentioning
confidence: 99%
“…Linear regression analysis was used to study the influence of penA allele type and other molecular determinants of resistance on the MIC cro and MIC pen values in detail. The application of this method to predict the MIC values of various antimicrobial drugs against N. gonorrhoeae has been described previously [ 30 , 31 , 32 ]. The main determinants affecting MIC cro have been shown to be five amino acid substitutions in PBP2 Ala311Val, Ala501Pro/Thr/Val, Asn512Tyr, Ala516Gly, and Gly542Ser (numeration of amino acids Asn513Tyr, Ala517Gly, and Gly543Ser is given in the paper), mutation of the mtrR promoter, substitutions of the Gly120 residue in the PorB protein, and the Leu421Pro substitution in PBP1 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of this method to predict the MIC values of various antimicrobial drugs against N. gonorrhoeae has been described previously [ 30 , 31 , 32 ]. The main determinants affecting MIC cro have been shown to be five amino acid substitutions in PBP2 Ala311Val, Ala501Pro/Thr/Val, Asn512Tyr, Ala516Gly, and Gly542Ser (numeration of amino acids Asn513Tyr, Ala517Gly, and Gly543Ser is given in the paper), mutation of the mtrR promoter, substitutions of the Gly120 residue in the PorB protein, and the Leu421Pro substitution in PBP1 [ 32 ]. Analysis of 182 Russian isolates showed that the presence of the mosaic type XXXIV penA allele and the Gly120Lys substitution in the PorB protein made the greatest contributions to the increase in the MIC cro .…”
Section: Discussionmentioning
confidence: 99%